MEDIA-POLITICAL DISCOURSE FROM A TEXTOLOGICAL VIEWPOINT - Harutyunyan, Rafayel (Armenian Folia Anglistika, 2022)
There are different research methods, techniques and strategies that are used to study the text. One of such methods is the method of textual analysis, a variety of study approaches used to analyze and comprehend a piece of writing. Understanding media-political texts and avoiding manipulation and information bias requires not only linguistic and extra-linguistic competence, but also awareness of different strategies.In the present paper, we are aimed to provide an overview of textual analysis as a research tool for studying incidents of manipulation in media news broadcasts from a textological perspective.
Keywords: manipulation; media discourse; political discourse; textual analysis; manipulative strategies and techniques; linguistic and extralinguistic means